Assessing the Neurodevelopmental Impact of Fluoxetine, Citalopram, and Paroxetine on Neural Stem Cell-Derived Neurons - Kimia Hosseini; Andrea Cediel-Ulloa; Mohamed H. AL-Sabri; Anna Forsby; Robert Fredriksson (MDPI AG, 2024)
Background/Objectives: Many pregnant women globally suffer from depression and are routinely prescribed selective serotonin reuptake inhibitors (SSRIs). These drugs function by blocking the re-uptake of serotonin by the serotonin transporter (SERT) into neurons, resulting in its accumulation in the presynaptic cleft. Despite a large amount of research suggesting a potential link to neurodevelopmental disorders in children whose mothers took these drugs during pregnancy, their possible adverse effects are still debated, and results are contradictory. On the other hand, there is an immediate need for improved cell-based models for developmental neurotoxicity studies (DNT) to minimize the use of animals in research. Methods: In this study, we aimed to assess the effects of clinically relevant concentrations of paroxetine (PAR), fluoxetine (FLX), and citalopram (CIT)-on maturing neurons derived from human neural stem cells using multiple endpoints. Results: Although none of the tested concentrations of FLX, CIT, or PAR significantly affected cell viability, FLX (10 µM) exhibited the highest reduction in viability compared to the other drugs. Regarding neurite outgrowth, CIT did not have a significant effect. However, FLX (10 µM) significantly reduced both mean neurite outgrowth and mean processes, PAR significantly reduced mean processes, and showed a trend of dysregulation of multiple genes associated with neuronal development at therapeutic-relevant serum concentrations. Conclusions: Transcriptomic data and uptake experiments found no SERT activity in the system, suggesting that the adverse effects of FLX and PAR are independent of SERT.